Noninvasive DW-MRI metrics for staging hepatic fibrosis and grading inflammatory activity in patients with chronic hepatitis B. - Fu, Fangfang; Li, Xiaodong; Liu, Qiuyu; Chen, Cuiyun; Bai, Yan; Shi, Dapeng; Sang, Jia; Wang, Kaiyu; Wang, Meiyun (Abdominal Radiology, 2021)
Purpose: To assess the value of various diffusion parameters obtained from monoexponential, biexponential, and stretched-exponential diffusion-weighted imaging (DWI) models for staging hepatic fibrosis (HF) and grading inflammatory activity in patients with chronic hepatitis B (CHB). Methods: 82 patients with CHB and 30 healthy volunteers underwent DWI with 13 b-values on a 3T MRI unit. The standard apparent diffusion coefficient (ADCst) was calculated using a monoexponential model. The true diffusion coefficient (Dt), pseudo-diffusion coefficient (Dp), and perfusion fraction (f) were calculated using a biexponential model. The distributed diffusion coefficient (DDC) and water-molecule diffusion heterogeneity index (α) were calculated using a stretched-exponential model. Receiver operating characteristic (ROC) curves were performed for diffusion parameters to compare the diagnosis performance. Results: The distributions of hepatic fibrosis stages and the inflammatory activity grades (METAVIR scoring system) were as follows: F0, n = 1; F1, n = 16; F2, n = 31; F3, n = 19; and F4, n = 15. A0, n = 1; A1, n = 14; A2, n = 46; and A3, n = 21. ADCst, Dt and DDC values showed negative correlation with the fibrosis stage (r = − 0.418, − 0.717 and − 0.630, all P < 0.001) and the inflammatory activity grade (r = − 0.514, − 0.626 and − 0.550, all P < 0.001). The area under the ROC curve (AUC) of Dt (AUC = 0.854, 0.881) and DDC (AUC = 0.794, 0.834) were significantly higher than that of ADCst (AUC = 0.637, 0.717) in discriminating significant fibrosis (≥ F2) and advanced fibrosis (≥ F3) (all P < 0.05). Although Dt (AUC = 0.867, 0.836) and DDC (AUC = 0.810, 0.808) showed higher AUCs than ADCst (AUC = 0.767, 0.803), there was no significant difference in their ability in detecting inflammatory activity grade ≥ A2/A3 (P > 0.05). Conclusions: Dt and DDC are promising indicators and outperform ADCst for staging HF. While both Dt and DDC have similar diagnostic performance compared with ADCst for grading inflammatory activity.